The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1136/pgmj.2011.118059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of losartan on proteinuria and urinary angiotensinogen excretion in non-diabetic patients with chronic kidney disease

Abstract: Losartan significantly decreased proteinuria and UAGT excretion, and preserved renal function in non-diabetic patients with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…These effects are triggered by signaling via ANG II type 1 receptor . Numerous clinical and experimental studies have revealed that activation of ANG II type 1 receptor by ANG II can account for upregulation/activation of NAD(P)H oxidase and oxidative stress and that intervention by AT1 receptor blockers (ARBs) shows efficacy in slowing the onset of kidney disease and/or slowing progression of CKD . In fact, an experimental study of spontaneous focal glomerulosclerosis rats has indicated that ARB treatment prevented nephropathy, suppressed oxidative stress, inflammatory process, and endoplasmic reticulum stress‐induced apoptosis as well as restored Nrf2 activation and expression of the antioxidant enzymes .…”
Section: Discussionmentioning
confidence: 99%
“…These effects are triggered by signaling via ANG II type 1 receptor . Numerous clinical and experimental studies have revealed that activation of ANG II type 1 receptor by ANG II can account for upregulation/activation of NAD(P)H oxidase and oxidative stress and that intervention by AT1 receptor blockers (ARBs) shows efficacy in slowing the onset of kidney disease and/or slowing progression of CKD . In fact, an experimental study of spontaneous focal glomerulosclerosis rats has indicated that ARB treatment prevented nephropathy, suppressed oxidative stress, inflammatory process, and endoplasmic reticulum stress‐induced apoptosis as well as restored Nrf2 activation and expression of the antioxidant enzymes .…”
Section: Discussionmentioning
confidence: 99%
“…Others (Kim et al 2011a, b; Lee et al 2011; Mao et al 2012) and we (Kobori et al 2009, 2010) recently reported that urinary AGT excretion rate could be a novel biomarker for the activity of the RAS in kidney. However, dynamics of urinary AGT in humans have not been fully elucidated yet.…”
Section: Discussionmentioning
confidence: 82%
“…With respect to proteinuria, previous studies demonstrated that RAS inhibitors provide superior renoprotection in subjects with high urinary protein excretion. [21]…”
Section: Discussionmentioning
confidence: 99%